Designing bevel preparation tool using inventor for the preparation of angles in welding process - Nasir, Nasir; Abdullah, M. A.; L., N. H (2021)
This study was performed to test the design and analyze the strength of the bevel preparation tool in the preparation of the workpiece for the welding process. The purpose of this study is to perform stress analysis of a product that can be used by the user in the process of providing bevel for plate work for the welding process. ADDIE's design model serves as a guide in the development of this product. The ADDIE model consists of five phases namely analysis phase, design phase, development phase, implementation phase, and evaluation phase. This study also involves Autodesk Inventor software to perform stress analysis in product evaluation of bevel preparation tool in the welding process. thus can find data on mises stress, 1st principal stress, 3rd principal stress, displacement, and safety factor. The simulation results showed that it could withstand 527.029MPa and a safety factor of 0.474357 ul up to 15 ul. In conclusion, the bevel preparation tool in the welding process is able to assist in the preparation of the corners and can withstand durability when applied to this product.